1986
DOI: 10.1007/bf01726920
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of atrial natriuretic factor release in man: Effect of water immersion

Abstract: The atrial natriuretic factors (ANF) have recently emerged as a novel hormonal system [3, 10] that may be implicated in extracellular volume homeostasis [9]. Recently, employing our highly sensitive radioimmunoassay [1], we have demonstrated elevated A N F plasma levels in patients with diseases involving pressure/volume overload [2, 6]. The physiologic regulation of ANF release in healthy subjects, however, needs further elucidation [7]. Water immersion causes an increase in central venous pressure due to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
1
13
0
2
Order By: Relevance
“…Epstein and others have demonstrated in numerous investigations that WI is a useful tool for the study of volume regulation (5): it increases central volume by shifting blood from peripheral vessels thus obviating the necessity of infusing volume expanders that might alter plasma composition. We demonstrated that WI rapidly increases ANF plasma levels in healthy human subjects (10). In the present study WI was used to investigate the response of ANF to acute volume Stimulation in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 70%
“…Epstein and others have demonstrated in numerous investigations that WI is a useful tool for the study of volume regulation (5): it increases central volume by shifting blood from peripheral vessels thus obviating the necessity of infusing volume expanders that might alter plasma composition. We demonstrated that WI rapidly increases ANF plasma levels in healthy human subjects (10). In the present study WI was used to investigate the response of ANF to acute volume Stimulation in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 70%
“…13 In W the local vasodilatation and general sympathetic activity seem to be proficiently balanced: from cardiac filling pressure through central blood shift ANP (Atrial Natriuretic Peptide) concentrations are elevated up to 2-3-fold. 32 The well-characterized ANP pathway regulates vascular tone -which is under sympathetic nervous system control -and renal sodium handling. ANP acts as a vasodilator via endothelial cells and promotes baroreflex-mediated activation.…”
Section: Discussionmentioning
confidence: 99%
“…see [4]). Furthermore it could be demonstrated in a previous study, that WI stimulates atrial natriuretic factor (ANF) in man [5] and thus seems to be a useful mean to study the physiological role of ANF in acute volume regulation.…”
Section: Renal and Hormonal Reactions During Water Imnmersion In Healmentioning
confidence: 99%